The World Almanac and book of facts 1996 - 4 0 16; Famighetti, Robert; 5 (Mahwah, New Jersey :;[New York] : World Almanac,;Distributed to the book trade by St. Martin's Press, 1995)
Presents thousands of facts about a wide variety of subjects. Includes the year in review, sports statistics, and a color section of world maps and flags.
Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Almanacs.;Almanacs.; 20; 2